Evaluation Of Dry And Dirty Bulk Cargo Handling Governance In Minimizing Potential Air Pollution At Marunda Port, Tanjung Priok. - Retno Hariyanti; Sri Purwantini; Sri Suharni; Aulia Uyun; Anggi Mawarsari (LPPM AKMI SUAKA BAHARI CIREBON, 2026)
Marunda Port, Tanjung Priok, has a high intensity of dry bulk cargo handling, particularly coal and sand, which may increase the risk of air pollution through dust and particulate emissions. Purpose – This study aims to evaluate the governance of dry and dirty bulk cargo handling, assess air pollution conditions, and identify mitigation measures implemented at Marunda Port. Methodology – A qualitative descriptive-analytical approach was applied through field observation, semi-structured interviews, documentation, and review of official institutional reports. Qualitative data were analyzed using the Miles and Huberman interactive model, while supporting quantitative data were examined descriptively by comparing cargo handling intensity, ISPU distribution, Ambient Air Quality Status Index (ISM), and pollutant indicators including PM10, PM2.5, SO₂, CO, O₃, NO₂, dust particulate, and Pb with applicable standards. Findings – The results show that cargo handling governance has been implemented through administrative verification, equipment inspection, SOP enforcement, water spraying, dust-control nets, and routine air quality monitoring. In 2024, Marunda Port handled an average of 129 loading/unloading activities and 773,147 MT of cargo per month. North Jakarta air quality was dominated by the “moderate” ISPU category, while ISM improved from 0.59 in 2023 to 0.51 in 2024. However, PM2.5 at the KBN gate exceeded the standard. Therefore, stricter supervision, improved dust-control facilities, and integrated stakeholder coordination are required